Overall thermal transfer value: a preliminary study of residential building in hot-humid climate / Norasikin Hussin ... [et al.] - Hussin, Norasikin; Yaakob, Yusli; Abd Razak, Azli; Baharum, Faizal (Penerbit UiTM (UiTM Press), 2025)
Malaysia buildings have high intensity of solar radiation and high daily air temperature. Due to excessive heat and high air temperature can cause discomfort, and the occupants need to use the air-conditioning system. The use of air-conditioning has influence to increasing the energy consumption in buildings. To tackle this issue, the Overall Thermal Transfer Value (OTTV) standard as an assessment tool is used to measure of heat gain in the building. OTTV standard is applicable to minimize energy consumption of air conditioning. This study aimed to investigate the OTTV in single terrace house. The method used in this study is by direct calculation. The OTTV was calculated for two cases, namely case study model A and model B. The study considered parameters of building envelope such as window-to-wall ratio. U value, glazing material, and fenestration orientation.